How the Freshwater Biodiversity Information System (FBIS) is supporting national freshwater fish conservation decisions in South Africa - Kajee, Mohammed; Henry, Dominic A. W.; Dallas, Helen F.; Griffiths, Charles L.; Pegg, Josephine; Van der Colff, Dewidine; Impson, Dean; Chakona, Albert; Raimondo, Domitilla C.; Job, Nancy M.; Paxton, Bruce R.; Jordaan, Martine S.; et al. (Frontiers in Environmental Science, 2023)
In South Africa, anthropogenic pressures such as water over-abstraction, invasive species impacts, pollution, land-use, and climate change have caused widespread deterioration of the health of river ecosystems. This comes at great cost to both people and biodiversity, with freshwater fishes ranked as the country’s most threatened species group. Effective conservation and management of South Africa’s freshwater ecosystems requires access to reliable and comprehensive biodiversity data. Despite the existence of a wealth of freshwater biodiversity data, access to these data has been limited. The Freshwater Biodiversity Information System (FBIS) was built to address this knowledge gap by developing an intuitive, accessible and reliable platform for freshwater biodiversity and ancillary data in South Africa. We describe how the system is being used to provide freshwater fish data to a national conservation decision-support tool – The Department of Forestry, Fisheries & Environment (DFFE) National Environmental Screening Tool. The Tool uses empirical and modelled biodiversity data to guide Environmental Impact Assessments of proposed developments. Occurrence records for 34 threatened freshwater fishes occurring in South Africa were extracted from the FBIS and verified by taxon specialists, resulting in 6 660 records being used to generate modelled and empirical national distribution layers. This will be the first inclusion of freshwater biodiversity data in the Screening Tool, and future iterations of the Tool will incorporate additional freshwater taxa. This case study demonstrates how systems like the FBIS can play a pivotal role in the data-to-decision pipeline through supporting data-driven conservation and management decisions at a national level.